Business conceptual design of photovoltaic installation for billboard lighting - Chrissandhi, Erico Sofyan; Pratiwi, Christa Dian; Hastuti, Tiwik Tri; Hisjam, Muhammad; Sutopo, Wahyudi (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
The usage of advertising as a medium for marketing products/services is used by various businesses to increase profits. The advertising medium mainly used is billboards, which still use fossil energy as an energy source. The Indonesian government's 2060 Net Zero Emission Program promotes using renewable energy (RE) as an energy source, such as photovoltaic (PV) as electrical energy from solar heat. As with RE, the development of PV still has problems in products and business, but PV is ready to be used as an energy source to reduce electricity bill costs. The business idea of PV installation in the advertising company sector emerged to support the government program Net Zero Emission, making advertising companies "green jobs" and absorbing human resources from vocational schools. Business conceptual design with value chains, business model canvas, and lean canvas expected can provide an overview of business opportunities with EBT for Indonesia that are environmentally friendly and energy independent.